Prosedur Pengurusan Izin Muat Barang Berbahaya Curah Padat Pada Kantor Utama Syahbandar Belawan Oleh PT. Pelayaran Karana Line Cabang Belawan - Putra Wandi; Syarifur Ridho; Yepta Vianus Marbun (Jurnal Publikasi Ilmu Manajemen, 2024)
This research aims to thoroughly examine the process undertaken by PT. Pelayaran Karana Line Branch Belawan in handling the permit procedure for loading bulk dangerous goods, specifically in the Medan Belawan area. The process begins when the marketing department provides information about the upcoming bulk dangerous goods cargo to be loaded onto the ship. Subsequently, the operational team or external service prepares a request letter to be submitted to the relevant agency, namely the Belawan Main Harbor Master's Office. For each permit submission, there are fees that must be paid. These fees are deposited into the state treasury as Non-Tax State Revenue (PNBP). PT. Pelayaran Karana Line Belawan, as a national shipping company, strives to build and maintain good relationships with related agencies. This is one of the strategies to ensure smooth handling of dangerous goods. In the permit processing procedure, document completeness is crucial. The required documents include a Permit Request Letter and a dangerous goods manifest. The completeness and accuracy of these documents are essential to ensure the permit processing proceeds smoothly and in accordance with applicable regulations.